An Analyzing RFM (Recency, Frequency, Monetary) Segmentation to Formulate Online Marketing Strategies : a Case Study of PT MMT - Gilang Kharisma Ramadhan Ibrahim; Jerry Heikal (Sean Institute, 2025)
In the current era of globalization, companies must be able to maintain a high level of competitiveness and enhance their performance standards to face the increasing intensity of business competition, particularly in Indonesia. PT MMT has utilized digital media, especially Instagram, to promote its services. The travel agency owner has observed a noticeable increase in customer engagement since adopting online platforms such as Instagram and the company's website. The background of this research is based on the phenomenon of a decline in the number of umrah pilgrims over the last six months of 2024. Therefore, a data-driven marketing approach is required to improve customer retention and expand market acquisition. This study aims to analyze customer segmentation at PT MMT using the RFM (Recency, Frequency, Monetary) method to determine an effective online marketing strategy in the Umrah travel industry. The research applies a quantitative approach with a total population of 861 transactions. Secondary data were obtained from PT MMT's sales reports and digital marketing records. The analysis technique uses RFM Scoring to classify customers into several segments: VIP, Loyal, Potential VIP, New Potential, At Risk, and Lost Gold. The findings indicate that the online marketing strategy should primarily focus on the Potential VIP segment. Furthermore, the implementation of RFM analysis enables PT MMT to gain deeper insights into customer needs and develop more targeted online marketing strategies.